Dalbergia ecastaphyllum (L.) Taub. and Symphonia globulifera L.f.: The Botanical Sources of Isoflavonoids and Benzophenones in Brazilian Red Propolis - Gari Vidal Ccana-Ccapatinta; Jennyfer Andrea Aldana Mejía; Matheus Hikaru Tanimoto; Milton Groppo; Jean Carlos Andrade Sarmento de Carvalho; Jairo Kenupp Bastos (Molecules, 2020)
The Brazilian red propolis (BRP) constitutes an important commercial asset for northeast Brazilian beekeepers. The role of Dalbergia ecastaphyllum (L.) Taub. (Fabaceae) as the main botanical source of this propolis has been previously confirmed. However, in addition to isoflavonoids and other phenolics, which are present in the resin of D. ecastaphyllum, samples of BRP are reported to contain substantial amounts of polyprenylated benzophenones, whose botanical source was unknown. Therefore, field surveys, phytochemical and chromatographic analyses were undertaken to confirm the botanical sources of the red propolis produced in apiaries located in Canavieiras, Bahia, Brazil. The results confirmed D. ecastaphyllum as the botanical source of liquiritigenin (1), isoliquiritigenin (2), formononetin (3), vestitol (4), neovestitol (5), medicarpin (6), and 7-O-neovestitol (7), while Symphonia globulifera L.f. (Clusiaceae) is herein reported for the first time as the botanical source of polyprenylated benzophenones, mainly guttiferone E (8) and oblongifolin B (9), as well as the triterpenoids β-amyrin (10) and glutinol (11). The chemotaxonomic and economic significance of the occurrence of polyprenylated benzophenones in red propolis is discussed.